(untitled) (Veterinary Science, 2019)
The use of management strategies, such as adjustment of grazing intensity and nitrogen fertilization, are fundamental for the success of animal production, in crop-livestock integration systems (IAG). The objective was to evaluate the effects of grazing intensity and nitrogen fertilization on the nutritional value of Italian ragweed pastures (Lolium multiflorum Lam.), individual performance and by area of steers Nelore x Charoláis IAG. A randomized block experimental design with 2 x 2 factorial application and three repetitions was used. The first factor was grass height: High Height 25 cm (AA) and Low Height 10 cm (BA). The second factor was the period of nitrogen fertilization applied at two different times in the system: N applied in the pasture (NP) and N applied in the grains crop (NG), in doses of 200 kg of N ha-1, forming 4 treatments: AANG, AANP, BANG and BANP. The grass height of Italian raigras (Lolium multiflorum Lam.) was regulated by continuous grazing with variable number of animals. With nitrogen fertilization in the pasture, it is possible to handle the Raigras ‘Winter star’ grasses with an average height of 12.5 cm. The accumulation rate and the total DM production were higher in AANP. Nitrogen fertilization of the pasture resulted in higher crude protein content, less of neutral detergent fiber and acid detergent fiber. With the advance of the grazing period and the pasture phenology, there was a decrease in crude protein and an increase in the neutral and acid detergent fiber. The average daily gain did not present a difference between treatments and was greater than 1.0 kg day-1, the average gain per area was greater in the BANP treatment